The Concept of Islamic Leadership in Building Organizational Governance with Integrity - Masruatus Saadah (Aafiyah: Jurnal Multidisiplin Ilmu, 2024)
Leadership with integrity has become a fundamental requirement in contemporary organizational governance amid increasing challenges related to corruption, abuse of power, unethical management, and declining public trust in institutions. Islamic leadership offers ethical and spiritual principles emphasizing justice, honesty, responsibility, transparency, accountability, and service-oriented leadership as essential foundations for organizational governance. This study aims to analyze the concept of Islamic leadership in building organizational governance with integrity and examine its relevance within modern organizational management. The research employs a qualitative descriptive approach through literature review and contextual analysis of Islamic leadership principles, organizational ethics, and governance theory. The findings indicate that Islamic leadership emphasizes moral responsibility, trustworthiness (amanah), justice (adl), consultation (shura), and exemplary conduct as central elements in organizational management. Islamic leadership also promotes participatory decision-making, ethical accountability, social responsibility, and employee empowerment to strengthen institutional integrity and organizational sustainability. Furthermore, the study reveals that implementing Islamic leadership values can contribute positively to transparency, organizational trust, professional ethics, and effective governance within both public and private institutions. Therefore, Islamic leadership principles remain highly relevant in developing organizations characterized by ethical responsibility, integrity, and sustainable social contribution in contemporary society.